Managerial social capital and dividend smoothing - García-Feijóo, Luis; Hossain, Md Miran; Javakhadze, David (Journal of Corporate Finance, 2021)
We investigate the influence of a previously unexamined managerial personal attribute, social capital, on a firm's propensity to smooth dividends. We document that greater managerial social capital is associated with a statistically and economically significant increase in dividend smoothing. The effect of social capital on dividend smoothing is stronger for financially constrained firms. We also find that social connections are positively associated with passive institutional ownership. Our results are robust to alternative model specifications, different variable measurement, and endogeneity tests. Overall, the findings are consistent with agency-based explanations for corporate dividend smoothing.